2020
DOI: 10.1002/anie.202014454
|View full text |Cite
|
Sign up to set email alerts
|

Inside Cover: The Conformational Equilibrium of the Neuropeptide Y2 Receptor in Bilayer Membranes (Angew. Chem. Int. Ed. 52/2020)

Abstract: NMR spectroscopy … …s heds light on receptor activation:M olecular switches are conserved motifs of Gprotein-coupled receptors that undergo structural changes during activation. Tr yptophan residues are often part of these molecular switches and thus provide insights in the activation mechanism of the molecule.I nt heir Research Article on page 23854, D. Huster and co-workers use NMR spectroscopy to monitor structural alterations of the neuropeptide Y 1 receptor with atomic resolution observable by changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The activation of a GPCR is accompanied by characteristic changes in the energy landscape of these proteins [ 54 ], resulting in dynamic alterations. In addition to the characteristic changes observed upon activation and G-protein or arrestin binding [ 20 , 21 , 22 , 23 , 24 ], the equilibrium dynamics of a GPCR is subject to changes [ 35 , 44 , 45 ]. Here, we probed how the fluctuations of Y1R reconstituted into DMPC membranes would change upon agonist binding and subsequent interaction with arrestin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The activation of a GPCR is accompanied by characteristic changes in the energy landscape of these proteins [ 54 ], resulting in dynamic alterations. In addition to the characteristic changes observed upon activation and G-protein or arrestin binding [ 20 , 21 , 22 , 23 , 24 ], the equilibrium dynamics of a GPCR is subject to changes [ 35 , 44 , 45 ]. Here, we probed how the fluctuations of Y1R reconstituted into DMPC membranes would change upon agonist binding and subsequent interaction with arrestin.…”
Section: Resultsmentioning
confidence: 99%
“…Under the latter conditions, backbone order parameters amounted to surprisingly low values between 0.57 and 0.67 depending on the host membrane, corresponding to remarkable backbone motional amplitudes of the C–H bond vectors of 47° to 40°. In a recent study, the site-specific order parameters of all Trp residues, mostly residing in α-helical secondary structures of the Y2R in DMPC membranes, were measured site-specifically using CP excitation with a 700 µs contact time [ 24 ]. This study reported Trp order parameters between 0.71 to 0.85 in the apo state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, desensitization processes on GPCRs have not yet been studied in as much detail as have activation processes. It will therefore be important to extend the NMR studies towards receptor desensitization to address, for example, biased agonism [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%